Differential Validity and Utility of Successive and Simultaneous Approaches to the Development of Equivalent Achievement Tests in French and English - Rogers, W. Todd; Gierl, Mark J.; Tardif, Claudette; Lin, Jie; Rinaldi, Christina (Alberta Journal of Educational Research, 2003)
Described in this article are the first three activities of a research program designed to assess the differential validity and utility of successive and simultaneous approaches to the development of equivalent achievement tests in the French and English languages. Two teams of multilingual/multicultural French-English teachers used the simultaneous approach to develop 70 items respectively for mathematics and social studies at the grade 9 level. The evidence gained from the pilot study suggests that the issue of differential item performance attributable to translation differences appears to be confounded by the presence of socioeconomic differences between the two groups of students. Consequently, the next activities of this research will be directed toward disentangling these two issues to obtain a clearer view of the efficacy of the simultaneous method in reducing differential group performance and enhancing linguistic and cultural decentering.